Women entrepreneurs’ intentions and challenges: a case of Bidayuh entrepreneurs in Kuching / Valeni Tia Basil - Basil, Valeni Tia (2014)
The numbers of women entrepreneurs are growing from time to time. Same goes to the Bidayuh Women Entrepreneurs. Many years back, the Bidayuh women only works as a housewife and farmer. But nowadays, they are starting to involve themselves in entrepreneurship. In Kuching, the number of Bidayuh Women Entrepreneurs are still little compared to others Bumiputera’s which is 60 entrepreneurs out of 5125 Bumiputera Entrepreneurs in Sarawak. But even though the number is little, but it is increasing. The present study investigates the entrepreneurial intentions and challenges faced by the Bidayuh Women Entrepreneurs and a research framework is constructed to identify the intentions that influence the start-up of a business and the most significant entrepreneurial challenges faced by the Bidayuh Women Entrepreneurs. The analysis is based on Bidayuh Women Entrepreneurs in Kuching with a quota sample of 52. The results of the study revealed that Push Factors influence the Bidayuh Women Entrepreneurs intention to start-up a business and the most significant challenges faced by them is access to resources. The study suggested that if the Bidayuh Women Entrepreneurs wants to improve themselves in their business, they need to attend trainings and short courses on entrepreneurship. Therefore, it is crucial for the Bidayuh Women Entrepreneurs to attend trainings to develop their entrepreneurial skills in order to become successful.